Analysis of Carbon Functional Groups through FTIR Patterns in The Preparation of Reduced Graphene Oxide (RGO) - Nur Aini Fauziyah; Dona Avrilia Kristanti; Putri Catur Kusumaningtyas; Primasari Cahya Wardhani; Pardi Sampe Tola; Teuku Andi Fadly (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The preparation of Reduced Graphene Oxide (RGO) through oil palm fiber biomass using a strong acid activation method with sulfuric acid (H2SO4) media, followed by application of microwave waves, is an interesting approach to obtain RGO. The study primarily focused on using the Fourier Transform Infrared (FTIR) spectroscopy technique to detect the formation of RGO based on changes in functional groups. The success of the formation of this RGO was confirmed by the presence of sharp and widening peak in the range of wave numbers 3254-3399 cm-1 which was OH-stretching. the longer the microwave wave is applied, the narrower the OH-stretching peak due to the removal of oxygen due to the application of microwave wave.